A Vascular-Network-Based Nonuniform Hierarchical Fault-Tolerant Routing Algorithm for Wireless Sensor Networks - Hongbing Li; Peng Gao; Qingyu Xiong; Weiren Shi; Qiang Chen (International Journal of Distributed Sensor Networks)
Fault tolerance is the key technology in wireless sensor networks which attracts many research interests. Aiming at the issue that the nodes' failures affect the network's stability and service quality, a vascular-network-based fault-tolerant routing algorithm is presented by nonuniform hierarchical clustering. According to the distribution characteristics of the vascular network and inspirations to the fault tolerance for wireless sensor networks, a mathematical model and network topology are, respectively, established. It applies the improved particle swarm optimization (IPSO) to the nonuniform hierarchical clustering, and multipaths are established between the neighbor hierarchical nodes based on the best-worst ant system (BWAS). It introduces the normalized values of the pheromone generated by the ants as the selection probabilities of transmitting paths to establish the hierarchical routing. Theoretical analysis and simulations show that the algorithm has higher packet receiving rates, lower average transmission delay, and balanced energy consumption. It has the good performance in fault tolerance and stability of data transmitting, and it avoids the hot issue in energy consumption and achieves the network load balance.